Ergonomics ablution (wudu') workstation design for shopping complex - Widia, Mirta; Amirul Asyraf, Jaafar (2021)
Ablution workstation is considered as one of the crucial public facilities especially in country with high Muslim population, but still lacking specifically regarding the ablution area (Besari et al.,2009). The design for the ablution workstation should consider and examine the element of humanities to maintain the law of Islam. For low-risk, secure and user-friendly settings, the ergonomic feature should be considered